Platform governance for sustainable development: Reshaping citizen-administration relationships in the digital age - Janowski, Tomasz (2018)
Changing governance paradigms has been shaping and reshaping the landscape of citizen-administration relationships, from impartial application of rules and regulations by administration to exercise its authority over citizens (bureaucratic paradigm), through provision of public services by administration to fulfil the needs of citizens (consumerist paradigm), to responsibility-sharing between administration and citizens for policy and service processes (participatory paradigm). The recent trend is the administration empowering citizens to create public value by themselves, through socio-technical systems that bring data, services, technologies and people together to respond to changing societal needs. Such systems are called “platforms” and the trend is called “platform paradigm”. The aim of this article is to offer a conceptual framework for citizen-administration relationships under the platform paradigm. While existing models of citizen-administration relationships mainly focus on specific types of relationships, e.g. citizen trust versus administrative transparency, or citizen satisfaction versus administrative performance, the proposed framework identifies a comprehensive set of relationships that explain how decisions by citizens or administration and the policy environment mutually agreed by them contribute to shaping such relationships and building individual and collective capacity for pursuing sustainable development. The framework comprises 15 types of relationships organized along the four governance paradigms. It is illustrated through the analysis of 11 case studies published in the current issue. Based on this analysis, the article also formulates some insights that are relevant to researchers and policymakers who intend to utilize platform governance for sustainable development.